Rekonstruksi Tata Kelola Maritim dan Kelestarian Religi: Strategi Pengentasan Kemiskinan Berbasis Masyarakat Hukum Adat di Situs Maudori, Kabupaten Supiori - Ngilamele, Rafles; Suhartono, Tony; Suryady, Robertus (LPPM Sekolah Tinggi Teologi Tabgha Batam, 2026)
Background: Supiori Regency, Papua, records an extreme poverty rate of 42.6% (2025) a paradox given its rich marine resources and historical-religious significance as the site of the first Gospel landing (1908). Technocratic development approaches have failed to address structural poverty by overlooking indigenous knowledge systems and institutional structures. Methods: This study employs a qualitative approach with an instrumental case study design. Data were collected through a Focus Group Discussion (FGD) minutes on the identification and mapping of the Indigenous Law Community (MHA) of West Supiori District (March 2026), in-depth interviews with key informants, participatory observation at the